Hubungan Antara Self-Talk Positif dan Communication Apprehension Pada Mahasiswa BKI IAIN Parepare - mustary, emilia (KOMUNIDA : Media Komunikasi dan Dakwah, 2020)
This study aimed to see the relationship between the frequency of positive self-talk and the level of communication apprehension experienced by colege students. This study used a quantitative approach with a correlational design. The research sample consisted of 75 students of the BKI IAIN Parepare Study Program, consisting of 15 male and 70 female. The data collection technique by providing a scale in the form of the Self-talk Scale from Brinhaupt, Hein, and Kramer (2009) for measuring the frequency of positive self-talk and the Personal Report of Communication apprehension (PRCA) scale from McCroskey (1994) for measure communication apprehension. The product moment analysis test is used to test the hypothesis by analyzing the relationship between the frequency of doing positive self-talk and the level of communication apprehension. The results showed that there was a relationship between the frequency of doing positive self-talk with the level of communication apprehension among students with a significance value of 0.000 (p <0.05) and a correlation coefficient value of -0.452. The more often students do positive self-talk, the lower level of communication apprehension they feel. The effective contribution given by the positive self-talk variable to the communication apprehension variable was 45.2%. The implication of this study shows that positive self-talk techniques can be used in improving students' personal competence in communication and can be applied to various communication situations, including the guidance and counseling process.